[Book review] Anti Selart (ed.), Baltic Crusades and Societal Innovation in Livonia, 1200–1350 - Gerner, Kristian (Journal of Northern Studies, 2024)
Review of: Anti Selart (ed.), Baltic Crusades and Societal Innovation in Livonia, 1200–1350 (The Northern World 93), Leiden: Brill 2020